2020
DOI: 10.1097/j.pain.0000000000002031
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture alleviates chronic pain and comorbid conditions in a mouse model of neuropathic pain: the involvement of DNA methylation in the prefrontal cortex

Abstract: Supplemental Digital Content is Available in the Text. Acupuncture treatment for 6-month period altered DNA methylation patterns, particularly in the prefrontal cortex, in a mouse model of chronic neuropathic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 77 publications
1
16
0
Order By: Relevance
“…Our results showed that EA treatment relieved the mechanical hyperalgesia and anxiety-and depressive-like behaviors. The results are consistent with the previous studies showing that EA has analgesic, antianxiety, and antidepressantlike effects on NeuP (Li et al, 2014;Jang et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that EA treatment relieved the mechanical hyperalgesia and anxiety-and depressive-like behaviors. The results are consistent with the previous studies showing that EA has analgesic, antianxiety, and antidepressantlike effects on NeuP (Li et al, 2014;Jang et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…(6) Acupuncture exerts analgesic effects by mediating mitogen-activated protein kinase (MAPK) signaling pathways, including the spinal cord p38/MAPK ( Fang et al, 2013 ; Liang et al, 2016 ), extracellular-signal-regulated kinase ( Choi et al, 2012 ; Park et al, 2014 ), c-Jun N-terminal kinase ( Lee et al, 2013 ), and nuclear factor kappa-B pathways ( Park et al, 2002 ). (7) Acupuncture exerts analgesic effects through epigenetic regulation of genes in tissues and cells, including DNA methylation ( Jang et al, 2021 ), histone modification ( Lai et al, 2012 ), and microRNA regulation ( Liu and Wu, 2017 ; Zou et al, 2019 ). These theories have provided a theoretical basis for evaluating the effectiveness of acupuncture in PHN treatment and have laid the foundation for follow-up research.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are many pain related journals, which indicates that acupuncture intervention on pain is being widely studied. [60][61][62][63][64][65][66][67][68][69][70][71][72] But the top productive journals on acupuncture for CP's average IF is not high (4.19). Therefore, the international influence of research on acupuncture for CP is relatively insufficient.…”
Section: Discussionmentioning
confidence: 99%